Using the Transtheoretical Model of Change to Understand High School Students’ Screen Time Behavior - Salwan Abed Laftah, Mohammed Baqer Habeeb Abd Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Objective(s): The aim of this study is to understand high school students’ screen time behavior. Methodology: Part of the study was an experimental randomized controlled trial used to guide this study. The study was conducted at Al-Wihdah High School for females in Al-Nasiriyah City. The study encompassed a simple random sample of 144 high school female students. The study instrument includes subjects’ sociodemographic characteristics of age, living arrangement, family’s socioeconomic status. It also includes the Transtheoretical Model of Change measures of Stages of Change for Screen Time Scale (Short Form) which includes five questions, each question represents one of the Stages of Change for Screen Time. It also includes Stages of Change for Screen Time Scale (Continuous Measure), the Processes of Change for Screen Time Scale, the Self-Efficacy for Screen Time Scale, and the Decisional Balance Scale for Screen Time. Data were collected using a self-reported method for the period from November 1st, 2021 to April 10th, 2022. Data were analyzed using the statistical package for social science (SPSS) for windows, version 26. Results: The study results revealed that the administered Transtheoretical Model of Change-Stage-matched intervention moved subjects from lower Stages of Change to higher ones. Conclusion: The administered Transtheoretical Model of Change-Stage-matched intervention stepped subjects to higher Stages of Change. Subjects in higher Stages of Change use more Processes of Change.